2019
DOI: 10.1177/0969141319879955
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial: Flexible sigmoidoscopy as an adjunct to faecal occult blood testing in population screening

Abstract: Objectives Flexible sigmoidoscopy screening at around age 60 can reduce colorectal cancer incidence. Insufficient evidence exists on flexible sigmoidoscopy at age 60 in a population being offered biennial faecal occult blood test screening from age 50. This randomized controlled trial assessed if flexible sigmoidoscopy would be an effective adjunct to faecal occult blood test. Methods In the Scottish Bowel Screening Programme between June 2014 and December 2015, 51,769 individuals were randomized to be offered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Thirty-three unique fair- to good-quality studies (n = 10 776 276) (published in 66 articles) were included to assess the effectiveness or comparative effectiveness of screening tests on CRC incidence and mortality. These included 2 prospective cohort studies (n = 436 927) that examined the effectiveness of screening colonoscopy, 4 RCTs (n = 458 002) that examined the effectiveness of flexible sigmoidoscopy with or without a FIT, 6 trials (n = 525 966) that examined the effectiveness of a gFOBT, and 1 prospective cohort study (n = 5 417 699) that examined the effectiveness of a FIT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three unique fair- to good-quality studies (n = 10 776 276) (published in 66 articles) were included to assess the effectiveness or comparative effectiveness of screening tests on CRC incidence and mortality. These included 2 prospective cohort studies (n = 436 927) that examined the effectiveness of screening colonoscopy, 4 RCTs (n = 458 002) that examined the effectiveness of flexible sigmoidoscopy with or without a FIT, 6 trials (n = 525 966) that examined the effectiveness of a gFOBT, and 1 prospective cohort study (n = 5 417 699) that examined the effectiveness of a FIT.…”
Section: Resultsmentioning
confidence: 99%
“…These included 2 prospective cohort studies (n = 436 927) that examined the effectiveness of screening colonoscopy, 4 RCTs (n = 458 002) that examined the effectiveness of flexible sigmoidoscopy with or without a FIT, 6 trials (n = 525 966) that examined the effectiveness of a gFOBT, and 1 prospective cohort study (n = 5 417 699) that examined the effectiveness of a FIT. In addition to 1 screening RCT (n = 98 678) that evaluated flexible sigmoidoscopy plus FIT vs flexible sigmoidoscopy alone, 20 studies (n = 471 860) that compared screening modalities were included. The magnitude of benefit in CRC mortality and cancer incidence among screening tests could not be directly compared because of major differences in the design of included studies for each test type (eg, trial vs observational study, intention to screen vs as screened, outcome metric reported).…”
Section: Resultsmentioning
confidence: 99%
“…Participation is lowest in the lowest socioeconomic groups, 5,7‐10 population with nonnative ethnicity, 5,8,9 those living without a partner, 5,8 with earlier nonparticipation 8 and with major chronic diseases 11 . The socioeconomic gradient is also important in sigmoidoscopy screening, where participation is lower than in faecal‐based screening 12,13 . However, it is unknown whether sociodemographic factors predict participation in faecal‐based and sigmoidoscopy screening differently.…”
Section: Introductionmentioning
confidence: 99%
“…11 The socioeconomic gradient is also important in sigmoidoscopy screening, where participation is lower than in faecal-based screening. 12,13 However, it is unknown whether sociodemographic factors predict participation in faecal-based and sigmoidoscopy screening differently.…”
Section: Introductionmentioning
confidence: 99%
“…1 In this edition of the journal, Steele et al report on a randomized controlled trial of the offer of guaiac faecal occult blood test (FOBT) alone or in conjunction with flexible sigmoidoscopy (FS) in people aged 60 in Scotland. 2 Compared with previous studies of FS, this trial had very low uptake: 17.8% overall, ranging from 7.4% among the most deprived women to 28.6% among the least deprived men.…”
mentioning
confidence: 60%